Air Pollution Zone Migrates South Driven by East Asian Winter Monsoon and Climate Change. Issue 10 (19th May 2021) - Zhao, Shuyu; Feng, Tian; Tie, Xuexi; Li, Guohui; Cao, Junji
Abstract: A variety of climatological indices have been established to illustrate the impact of climate change on air pollution in China, but major facts for causing variations of air pollution attributed to climate change are still unclear. Here, using in‐situ PM2.5 (particles with the aerodynamic diameter less than 2.5 μm) measurement, atmospheric reanalysis data and a chemical transport model, we show that meridional distribution of PM2.5 loadings is strongly modulated by the intensity of East Asian winter monsoon (EAWM). The EAWM drives the heavily polluted zone in eastern China to migrate southward, i.e., under stronger EAWM, more southward migration of air pollution occurs. We expect that the migration will likely re‐distribute carbon sources‐ and sinks‐related ecosystem, posing a new challenge for the Chinese government, who needs to implement region‐different emission reduction plans in the future, to mitigate air pollution and to go carbon neutral. Plain Language Summary: The relationship between the severe air pollution in China and climate has drawn much attention from scientific community, which still remains unclear. In this study, we present that air pollution with high PM2.5 loadings in winter, China is significantly modulated by East Asian winter monsoon (EAWM) based on ambient PM2.5 measurements, atmospheric reanalysis data and the GEOS‐Chem model. We find that the change in EAWM intensity dominates the location of heavily polluted zone and its meridional distribution. Stronger EAWM generally drives the zone to migrate more southward in eastern China, highlighting the predominant role of EAWM in redistributing air pollution of China during wintertime. Under climate change, the inter‐annual variability and decadal oscillation of EAWM projected by CMIP5 and CMIP6 models indicate a southward migration of the heavily polluted zone in next decades, probably approaching the Yangtze River Delta. This result may pose new challenges in air pollution control for local governments in different regions regarding climatic influence. Key Points: East Asian winter monsoon strongly modulates PM2.5 levels meridionally in eastern China Under climate change, the heavily polluted zone will likely move southward to Yangtze River Delta in the next decades China needs to implement regional‐different emission reduction measures regarding to the influence of climate change